Facile synthesis of MOF-derived ultrafine Co nanocrystals embedded in a nitrogen-doped carbon matrix for the hydrogen evolution reaction. Issue 75 (28th July 2016) - Zheng, Fangcai; Xia, Hongyu; Xu, Shihao; Wang, Rencui; Zhang, Yuanguang
Abstract : Non-precious metal-based catalysts with low cost and rich reserves are emerging as promising alternatives for Pt-based catalysts for the hydrogen evolution reaction (HER). Abstract : Non-precious metal-based catalysts with low cost and rich reserves are emerging as promising alternatives for Pt-based catalysts for the hydrogen evolution reaction (HER). Herein, we reported a facile and large-scale strategy for Co nanocrystals embedded in a nitrogen-doped carbon matrix through direct carbonization of Co-based metal–organic frameworks (MOFs) in N2 . After carbonization, the ultrafine Co nanocrystals are well dispersed in the nitrogen-doped carbon matrix. We further studied their electrocatalytic properties toward the HER in acidic media and found that the as-prepared catalyst exhibited enhanced catalytic activity and stability.